IMPROVING ECONOMIC METHODS OF AGRICULTURAL DEVELOPMENT IN THE REPUBLIC OF KAZAKHSTAN - Аinash Nurgaliyeva; Alexey Titkov; Dontsov S.S.; Мadina Karimbergenova; Gulmira Bayandina (Academic Journal of Physical and Chemical Sciences, 2020)
The article is devoted to modern trends and relevant problem-specific aspects of the development of the agricultural industry of the Republic of Kazakhstan. Particular attention is focused on the modern sectoral structure of the agricultural sector, the dynamics of gross output in agriculture, the structure of agricultural production, and budgeting for the agricultural sector. As part of the analysis and research, a SWOT analysis of the trends in the functioning of the agricultural sector of the economy of Kazakhstan was developed. The purpose of the article is to develop a set of systemic economic tools for agricultural reform in the Republic of Kazakhstan. The priorities of the target software, the need for the formation of high-quality staffing for the agricultural industry, the pursuit of an effective migration policy, the introduction of effective rental relations in the system of functioning of agricultural territories, the maximum involvement of agricultural land in the circulation with their subsequent intensive development are identified as the main priorities of agricultural development. The main research methods were - comparison, analogy, analysis and synthesis, a systematic approach, a forecasting method, induction and deduction methods, a statistical method, a hypothesis design method. The results of scientific research can find practical application at the national level and in the system of functioning of regional agrarian territories and agricultural clusters, focused on the application of innovations and new technologies.